Immune Checkpoint Inhibition in Non-Melanoma Skin Cancer: A Review of Current Evidence - Stonesifer, Connor J.; Djavid, A. Reza; Grimes, Joseph M.; Khaleel, Alexandra E.; Soliman, Yssra S.; Maisel-Campbell, Amanda; Garcia-Saleem, Tiffany J.; Geskin, Larisa J.; Carvajal, Richard D. (Frontiers in Oncology, 2021)
Recent advances in the field of immuno-oncology have translated into breakthrough treatments for many solid and hematological malignancies. The prior study of immunotherapy in dermatologic oncology has largely focused on cutaneous melanoma. However, recent focus has shifted to the use of immunotherapy to treat non-melanoma skin cancers (NMSCs), such as basal cell carcinoma (BCC), cutaneous squamous cell carcinoma (cSCC), and Merkel cell carcinoma (MCC). NMSCs represent the most ubiquitous cancers globally and, while they have a lower propensity to develop into advanced disease than cutaneous melanoma, their absolute mortality burden has recently surpassed that of melanoma. Patients with advanced NMSC are now benefiting from the successes of immunotherapy, including checkpoint inhibition with anti-CTLA-4 and anti-PD-1 monoclonal antibodies. In this review, we discuss the existing clinical evidence for immunotherapy in the treatment of NMSCs, with an emphasis on checkpoint inhibitor therapies. We highlight key studies in the field and provide up-to-date clinical evidence regarding ongoing clinical trials. We also review future study directions for immunotherapy as a therapeutic approach for NMSCs.